(untitled) (International Journal of Environmental Sciences, 2025)
In this study, we present a 40 year old male, who sustained an injury of the left knee and sought medical advice becauseof continuous pain. Based on the clinical examination and MRI the diagnose was a partial tear of the quadriceps tendon, consisting of a full thickness tear of the distal rectus femoris tendon sheath and a partial tear of theintermediate layer of quadriceps tendon. Due to the good muscle tone and absent functional deficit, a non-surgical management plan was planned and executed. The treatment consisted of a long knee brace, a period of non-weight bearing followed by protected weight bearing and gradual return to strength training. In order to decrease the load of rectus femoris muscle and to prevent reinjury, core stability exercises were also implemented with good functional outcome. We report the case for its rare incidence and the suggested non-surgical treatment with good outcome. We also present the current literature concerning mechanism and conservative management of extensor mechanism ruptures.